PENGEMBANGAN LKPD TEMPE KEMUL (KETERAMPILAN MEMBACA, MENULIS, DAN BERHITUNG PERMULAAN) UNTUK PESERTA DIDIK KELAS I - Lola Dwi Rapinka; Sholehuddin Sholehuddin; Sriyanti Rahmatunnisa (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to develop TEMPE KEMUL LKPD (Reading, Writing, and Beginning Counting Skills) for class I students. This research is a research and development research by applying the ADDIE model. This model consists of five stages, namely analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The subjects in this study were students of class I MI Muhammadiyah Kalibeber Mojotengah Wonosobo Central Java. The data analysis used is descriptive quantitative and qualitative. The results showed that the assessments included 1) material expert validation getting 82% including the very valid category, 2) expert validation getting 98% including the very valid category, 3) media expert validation getting 78% validity including in the valid category. Student teacher practicality assessment 1) teacher practicality test, getting 92% including very practical category, 2) small group practicality test, getting 97% including very practical category, 3) large group practicality test, reaching 99% including very practical category. Based on these data, the TEMPE KEMUL LKPD for learning reading, writing, and arithmetic skills is suitable for use.